2017
DOI: 10.1186/s12890-017-0388-4
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial and transesophageal fine-needle aspiration using a single ultrasound bronchoscope in the diagnosis of locoregional recurrence of surgically-treated lung cancer

Abstract: BackgroundThe present study sought to evaluate the usefulness of EBUS-TBNA in the diagnosis of locoregional recurrence of lung cancer in a cohort of lung cancer patients who were previously treated surgically, and describe our initial experience of EUS-B-FNA in this clinical scenario.MethodsWe retrospectively studied the clinical records of all patients with a previous surgically-treated lung cancer who were referred to our bronchoscopy unit after suspicion of locoregional recurrence. The diagnostic sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Over the last years, EBUS-TBNA is currently proposed as the first choice in the diagnosis of loco-regional relapse of lung cancer since in such instances, the mediastinal area and altered postoperative fibrotic mediastinum make other invasive diagnostic procedures as transcervical extended mediastinal lymphadenectomy and video-assisted mediastinal lymphadenectomy, challenging and unsafe [4, 7, 8]. “Xiauhi” comparing diagnostic yield of EBUS-TBNA and VAM in mediastinal LN staging in lung cancer confirmed that both techniques have similar performance, with EBUS-TBNA being less invasive, better tolerated, and with fewer complications [9].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, EBUS-TBNA is currently proposed as the first choice in the diagnosis of loco-regional relapse of lung cancer since in such instances, the mediastinal area and altered postoperative fibrotic mediastinum make other invasive diagnostic procedures as transcervical extended mediastinal lymphadenectomy and video-assisted mediastinal lymphadenectomy, challenging and unsafe [4, 7, 8]. “Xiauhi” comparing diagnostic yield of EBUS-TBNA and VAM in mediastinal LN staging in lung cancer confirmed that both techniques have similar performance, with EBUS-TBNA being less invasive, better tolerated, and with fewer complications [9].…”
Section: Discussionmentioning
confidence: 99%
“…According to a literature review, Kim J. et al [ 28 ] showed high diagnostic value and high suitability for EGFR mutation analysis with regard to re-biopsy in patients with previously treated lung cancer. Sanz-Santos J. et al [ 29 ] proved EBUS-TBNA is an accurate procedure for the diagnosis of locoregional recurrence of surgically treated lung cancer. Although they all investigated the role of EBUS TBNA in recurrent lung cancer, no associated outcomes were discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Benign adrenal adenomas are also common [8]. PET scan is not very useful in differentiating benign from malignant lesion [9]. The cytology is thus important for patients with carcinoma of lung and adrenal lesions.…”
Section: Discussionmentioning
confidence: 99%